Sequência didática para o ensino médio sobre o tempo: breves implicações filosóficas sobre o tempo e a teoria da relatividade restrita - Silva Sobrinho, Paulo Roberto Ferreira da (2022)
When studying physics, we are educated with Newton's equations, which underlie the dynamics of motion, Maxwell's equations, which describe electromagnetic waves, Schrodinger's equations, which underlie quantum physics, and Quantum Field Theory which describes dynamics. of atomic and subatomic particles. The important thing to realize is that physics is a science of how things evolve over time, but the strangest thing about it all is that its nature is the greatest of mysteries. In the eventual work, brief reflections on time will be presented from ancient thinkers to Einstein's Special Theory of Relativity, since this is a theory built to explain space and time. A proposal for a Potentially Significant Teaching Unit (UEPS) will be applied with the help of concept maps in order to facilitate the teaching of this fascinating and mysterious content to high school students. The classes were applied during the Covid-19 pandemic period, initially planned for remote teaching, however, the new measures adopted by the Government of the State of Amazonas made it possible to apply the product in person.